STUDI SIKUENSTRATIGRAFI BERDASARKAN HASIL ANALISIS DATA PALINOLOGI PADA SUMUR Y, CEKUNGAN SUMATERA SELATAN - Rizki Ramadhan; Hadi Nugroho; Yoga Aribowo; Panuju Panuju (Geological Engineering E-Journal, 2013)
Palynology is a study of biostratigraphy for determining relative age and depositional environment basedon the abundance of palynomorf. Palynology study develompent in Indonesia is still could be more increasedalong with more oil and gas exploration moved to transitional environtment.Study of palynology in stratigraphy is aiming to determine relative age and depositional environment.Besides, palynology could also determine sequence stratigraphy in a large scale of study based on palynomorfpercentage. The study of sequence stratigraphy based on palynomorf percentage has been done in Well-Y, SouthSumatra basin.The method of this research is descriptive method through the microscopic observation on sample 1 - 14from 1400 m depth Y-Well’s cutting and quantitative method calculation and analysis method from thisobservation and calcuation could determine the percentage of each palynomorf. This percentage lead to a trendthen interpretated into several sequencestratigraphy.From this observation, it can be determined characteristic zone of this well. The characteristic zone ofpalynology in this well is divided into 3 zones of palynology; Proxapertites operculatus Zone, Flocshuetziameridionalis Zone, and Stenoclaeniidites papuanus Zone. Each zone shows the characteristic of age fromEocene to Pliocene and also depositional environment from delta plain to pro delta. From palynomorfpercentage trend, we may also see the pattern of sequece stratigraphy works in this depth. The percentage trendshows the time whether sea level fall at the minimum percentage of palynomorf and sea level rise at themaximum percentage of palynomorf. The trend shows the sequence with sequence boundary lying in the startand the end of the sequence and also transgressive surface indicates the sea level start rise. Overall, this wellhas 5 sequences based on this trend; sequence a, sequence b, sequence c, sequence d, and sequence e and all thesequences are bordered by sequence boundary.